2014
DOI: 10.1371/journal.pone.0113220
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Autophagy Marker Protein Atg8 Reveals Atypical Features of Autophagy in Plasmodium falciparum

Abstract: Conventional autophagy is a lysosome-dependent degradation process that has crucial homeostatic and regulatory functions in eukaryotic organisms. As malaria parasites must dispose a number of self and host cellular contents, we investigated if autophagy in malaria parasites is similar to the conventional autophagy. Genome wide analysis revealed a partial autophagy repertoire in Plasmodium, as homologs for only 15 of the 33 yeast autophagy proteins could be identified, including the autophagy marker Atg8. To ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 84 publications
8
66
0
Order By: Relevance
“…1410,1411 Note that although the lysosomal protease inhibitors E64 and pepstatin block lysosomal degradative activity in Plasmodium, these inhibitors do not affect ATG8 levels and associated structures, suggesting a need for alternate methodologies to investigate autophagy in this model system. 1412 In conventional autophagy, the final destination of autophagosomes is their fusion with lysosomes for intracellular degradation. However, T. gondii and certain stages of Plasmodium (insect and hepatic) lack degradative lysosomes, which makes questionable the presence of canonical autophagosomes and a process of autophagy in these parasites.…”
Section: Protistsmentioning
confidence: 99%
“…1410,1411 Note that although the lysosomal protease inhibitors E64 and pepstatin block lysosomal degradative activity in Plasmodium, these inhibitors do not affect ATG8 levels and associated structures, suggesting a need for alternate methodologies to investigate autophagy in this model system. 1412 In conventional autophagy, the final destination of autophagosomes is their fusion with lysosomes for intracellular degradation. However, T. gondii and certain stages of Plasmodium (insect and hepatic) lack degradative lysosomes, which makes questionable the presence of canonical autophagosomes and a process of autophagy in these parasites.…”
Section: Protistsmentioning
confidence: 99%
“…Using the ubiquitin-like protein ATG8 (PF3D7_1019900) as a marker, researchers have demonstrated punctate staining and partial co-localization with the apicoplast marker acyl carrier protein (ACP, PF3D7_0208500). In these studies, ART treatment decreased PfATG8 levels as evidenced by a decrease in intensity in immunofluorescence assays and Western blot, while the number of vesicles remained the same [71, 72]. However, treatment with the lysosomal Na + /H + pump inhibitor Bafilomycin A1 or lysosomal cysteine protease inhibitor E64d did not lead to accumulation of ATG8.…”
Section: The Roles Of Ubiquitin Ligases and Deubiquitinating Enzymes mentioning
confidence: 99%
“…Autophagy is a catabolic process performed by eukaryotic cells in order to maintain homeostasis and to degrade unwanted or toxic cellular content, such as misfolded proteins . The autophagy pathway has been demonstrated to be important for various functions in yeast and humans, but studies in the past five years have also shown that autophagy is necessary in human pathogens, such as Plasmodium …”
Section: Discussionmentioning
confidence: 99%
“…Our PTA compounds were designed to interfere with the Atg8–Atg3 protein–protein interaction and thereby prevent the lipidation of Atg8. Only this lipidated form of Atg8 is active: it participates in elongation of the autophagosomal membrane in higher eukaryotes, and is the predominant species in Plasmodium …”
Section: Discussionmentioning
confidence: 99%